Systematic Literature Review on New Product Development Issues in a Supply Chain Management - Ramadini, Khairunnisa; Hakim, Muhammad Alief Syuja'; Septyati, Widya (Jurnal Manajemen dan Inovasi (MANOVA), 2025)
Objective – This research aims to systematically review and synthesize research on New Product Development (NPD) from a Supply Chain Management (SCM) perspective, identifying dominant themes, research methods, and future directions. Design/methodology/approach – A systematic literature review (SLR) using secondary data consisting of 30 international journals related to new product development from a supply chain perspective. The selection of international journals is following the discussion contained in the research conducted by researchers related to new product development and its relationship to the supply chain, or journals that examine the causal relationship between the two. Findings – The review reveals that case study is the most frequently employed method, accounting for over half of the studies. Key research themes include supply chain configuration, customer fit, framework development, decision support, supplier collaboration, risk management, and sustainable SCM. A notable shift is observed from product-focused innovation toward more customer-driven and collaborative approaches. Modeling approaches such as Mixed Integer Linear Programming (MILP) have begun to incorporate uncertainty into NPD decisions, though their application remains limited. Research limitations/implications – The literature remains concentrated in manufacturing sectors and developed regions, limiting the generalizability of many conceptual frameworks. Additionally, methodological diversity remains low, with few studies employing advanced quantitative or hybrid approaches. Practical implications – The study provides insights for managers and practitioners on aligning NPD with supply chain strategies. It highlights the need for adaptable and resilient SCM configurations to support rapid, customer-focused product development. Originality/value – This review offers a comprehensive map of the current academic landscape on NPD in SCM, identifies methodological and thematic gaps, and provides a foundation for future cross-industry, multidisciplinary, and sustainability-oriented research.